PERENCANAAN KEMITRAAN LEMBAGA PENDIDIKAN PROFESI DAN KEWIRAUSAHAAN (LPPK) BHAKTI NUSA SEMARANG DENGAN INDUSTRI DUNIA KERJA - Maylani Wening Hapsari; Muarifuddin Muarifuddin (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the partnership planning between LPPK Bhakti Nusa and the workforce, the forms of partnership, as well as the supporting and inhibiting factors. This study employs a descriptive qualitative approach. Data were collected through semi-structured interviews with the Director of LPPK Bhakti Nusa, the Head of the Academic Division, and two industry partner representatives, as well as through a document review of the MoU, tracer study data, OJT logbooks, and other partnership documents. Data validity was ensured through triangulation of sources and techniques. Data analysis included data reduction, data presentation, and drawing conclusions. The research results indicate that LPPK Bhakti Nusa’s partnership planning encompasses four stages: identifying partnership program needs based on demand from the cruise ship and hospitality industries; analyzing the potential of prospective partners using criteria for four- and five-star hotels; evaluating previous collaboration outcomes; and developing an action plan. Forms of partnership include teaching collaboration through the involvement of guest instructor, On-the-Job Training (OJT), and graduate placement through partner hotels, P3MI, and cruise ship agencies. This study examines partnership planning at LPPKs in the hospitality sector that is responsive to international industry standards and can serve as a reference for similar non-formal educational institutions.